Predictors of Outcomes in Patients With Mild Ischemic Stroke Symptoms: MaRISS. Issue 6 (5th May 2021) - Romano, Jose G.; Gardener, Hannah; Campo-Bustillo, Iszet; Khan, Yosef; Tai, Sofie; Riley, Nikesha; Smith, Eric E.; Sacco, Ralph L.; Khatri, Pooja; Alger, Heather M.; Mac Grory, Brian; Gulati, Deepak; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Although most strokes present with mild symptoms, these have been poorly represented in clinical trials. The objective of this study is to describe multidimensional outcomes, identify predictors of worse outcomes, and explore the effect of thrombolysis in this population. Methods: This prospective observational study included patients with ischemic stroke or transient ischemic attack, a baseline National Institutes of Health Stroke Scale (NIHSS) score 0 to 5, presenting within 4.5 hours from symptom onset. The primary outcome was a 90-day modified Rankin Scale score of 0 to 1; secondary outcomes included good outcomes in the Barthel Index, Stroke Impact Scale-16, and European Quality of Life. Multivariable models were created to determine predictors of outcomes and the effect of alteplase. Results: A total of 1765 participants were included from 100 Get With The Guidelines-Stroke participating hospitals (age, 65±14; 42% women; final diagnosis of ischemic stroke, 90%; transient ischemic attack, 10%; 57% received alteplase). At 90 days, 37% were disabled and 25% not independent. Worse outcomes were noted for older individuals, women, non-Hispanic Blacks and Hispanics, Medicaid recipients, smokers, those with diabetes, atrial fibrillation, prior stroke, higher baseline NIHSS, visual field defects, and extremity weakness. Similar outcomes were noted for the alteplase-treated and untreated groups. Alteplase-treated patients were younger (64±13 versus 67±1.4) with higher NIHSS (2.9±1.4 versus 1.7±1.4). After adjusting for age, sex, race/ethnicity, and baseline NIHSS, we did not identify an effect of alteplase on the primary outcome but did find an association with Stroke Impact Scale-16 in the restricted sample of baseline NIHSS score 3–5. Few symptomatic intracerebral hemorrhages were recorded (<1%). Conclusions: A large proportion of stroke patients presenting with low NIHSS have a disabled outcome. Baseline predictors of worse outcomes are described. An effect of alteplase on outcomes was not identified in the overall cohort, but a suggestion of efficacy was noted in the NIHSS 3–5 subgroup. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02072681.